Evaluating the Feasibility and Effectiveness of an Interdisciplinary Verbal De-Escalation and Implicit Bias Check Training for Agitation Management in the Emergency Department - Carreras Tartak JA; Rodriguez G; Schwid M; Meeker MA; Thomas MD; Roy HJ; Dadabhoy FZ; Molina M; Chary A; Bukhman AK; Im DD; Temin ES; et al. (Risk Management and Healthcare Policy)
Jossie A Carreras Tartak,1 Giovanni Rodriguez,2 Madeline Schwid,3 Melissa A Meeker,2 Matthew D Thomas,4 Harold J Roy,4 Farah Z Dadabhoy,5 Melanie Molina,6 Anita Chary,7,8 Alice K Bukhman,9,10 Dana D Im,9,10 Elizabeth S Temin,2 Wendy L Macias-Konstantopoulos2,11 1Department of Emergency Medicine, Beth Israel Deaconess Medical Center, Boston, MA, USA; 2Department of Emergency Medicine, Massachusetts General Hospital, Boston, MA, USA; 3Department of Emergency Medicine, University of Rochester, Rochester, NY, USA; 4Department of Police and Security, Massachusetts General Hospital, Boston, MA, USA; 5Department of Anesthesiology, Perioperative and Pain Medicine, Beth Israel Deaconess Medical Center, Boston, MA, USA; 6Department of Emergency Medicine, University of California, San Francisco, CA, USA; 7Department of Emergency Medicine, Section of Health Services Research, Department of Medicine, Baylor College of Medicine, Houston, TX, USA; 8Center for Innovations in Quality, Effectiveness and Safety, Michael E. DeBakey VA Medical Center, Houston, TX, USA; 9Department of Emergency Medicine, Brigham and Women’s Hospital, Boston, MA, USA; 10Department of Emergency Medicine, Brigham and Women’s Faulkner Hospital, Boston, MA, USA; 11Center for Social Justice and Health Equity, Department of Emergency Medicine, Massachusetts General Hospital, Boston, MA, USACorrespondence: Jossie A Carreras Tartak, Beth Israel Deaconess Medical Center, Department of Emergency Medicine, Rosenberg Building, One Deaconess Road, 2nd Floor, Boston, MA, 02215, USA, Tel +1 617-754-2339, Fax +1 617-754-2350, Email jossie.a.carreras@gmail.comPurpose: Recent scholarship has revealed racial disparities in emergency department (ED) physical restraint use in agitation management. We implemented an interdisciplinary educational program that integrates discussions about the role of bias in physical restraint use with workplace violence (WPV) prevention strategies to increase awareness of implicit bias and comfort with verbal de-escalation among ED staff.Patients and Methods: In partnership with hospital security at a large urban academic medical center, we developed a 1-hour online WPV prerequisite course followed by a 2-hour multi-modal, in-person training consisting of 40 minutes each of didactics, an interactive defensive skills workshop, and case-based simulations with structured debriefings. From September 2022 to June 2023, all patient-facing ED staff were invited to participate and received a $100 gift card for program completion. Participants rated their confidence and comfort in various aspects of agitation management on a 5-point Likert scale before and immediately after via pre- and post-training surveys. Wilcoxon matched-pairs tests were employed for analysis.Results: Of 91 participants, 72 (79%) completed the pre- and post-training surveys. Representing a wide range of ED role groups, 74% of participants were clinical staff and a majority had 0– 5 years of experience (65%). Among all participants, there was a statistically significant improvement in confidence and comfort with the various aspects of agitation management across all 11 questions (p< 0.001). A similar change was observed among the clinical staff (p< 0.001), however, the degree of improvement observed among those with greater than 5 years of experience was less dramatic than among clinical staff with 0– 5 years of experience.Conclusion: Interdisciplinary multi-modal training can improve confidence and comfort with verbal de-escalation and implicit bias checks in team-based agitation management. Additional research is needed to understand if such integrated training can also reduce physical restraint use, racial disparities in restraint use, and WPV events.Keywords: physical restraints, psychiatry, emergency medicine, implicit bias, de-escalation training, quality improvement, education, agitation, workplace violence